Prevention and treatment of anticipatory chemotherapy‐induced nausea and vomiting in pediatric cancer patients and hematopoietic stem cell recipients: Clinical practice guideline update. Issue 5 (8th March 2021) - Patel, Priya; Robinson, Paula D.; Devine, Katie A.; Positano, Karyn; Cohen, Marie; Gibson, Paul; Holdsworth, Mark; Phillips, Robert; Spinelli, Daniela; Thackray, Jennifer; van de Wetering, Marianne; Woods, Deborah; et al.
Abstract: This 2021 clinical practice guideline update provides recommendations for preventing anticipatory chemotherapy‐induced nausea and vomiting (CINV) in pediatric patients. Recommendations are based on systematic reviews that identified (1) if a history of acute or delayed CINV is a risk factor for anticipatory CINV, and (2) interventions for anticipatory CINV prevention and treatment. A strong recommendation to optimize acute and delayed CINV control in order to prevent anticipatory CINV is made. Conditional recommendations are made for hypnosis, systematic desensitization, relaxation techniques, and lorazepam for the secondary prevention of anticipatory CINV. No recommendation for the treatment of anticipatory CINV can be made.